Bariatric surgery in liver cirrhosis - Mehdorn, A. S.; Moulla, Y.; Mehdorn, M.; Dietrich, A.; Schönfels, W.; Becker, T.; Braun, F.; Beckmann, J. H.; Linecker, M. (Frontiers in Surgery, 2022)
IIntroduction Obesity is frequently associated with its hepatic manifestation, the non-alcoholic fatty liver disease (NAFLD). The most effective treatment for morbid obesity is bariatric surgery (BS) also improving NAFLD and liver function. In patients where NAFLD has already progressed to liver cirrhosis, BS can be considered as a high-risk procedure. Hence, consideration of the procedure and the most proper timepoint is crucial. Material and Methods Obese patients suffering from NAFLD who underwent BS from two German University Medical Centers were retrospectively analyzed. Results Twenty-seven patients underwent BS. Most common procedures were laparoscopic Roux-en-Y-gastric (RYGB) and laparoscopic sleeve gastrectomy (SG). All patients suffered from liver cirrhosis Child A. A preoperative transjugular portosystemic shunt (TIPS) was established in three patients and failed in another patient. Postoperative complications consisted of wound healing disorders (n=2), anastomotic bleeding after RYGB (n=1) and leak from the staple line (n=1). This patient suffered from an intraoperatively detected macroscopic liver cirrhosis. Excess weight loss was 73% and 85% after one and two years, respectively. Two patients suffered from postoperative aggravation of their liver function, resulting in a higher Child-Pugh score while three patients no longer needed to be on the waiting list for a liver transplantation. Conclusion BS leads to weight loss, both after SG and RYGB, and potentially improvement of liver function in liver cirrhosis. These patients need to be considered with care when evaluated for BS. Preoperative TIPS-implantation may reduce the perioperative risk in selected patients.